Meningkatkan Kepedulian Masyarakat Terhadap Sampah dan Solusi Pengolahan Sampah Plastik dengan Eco brick - Cynthia Salim; Sisilia Christianti; Supryadi Supryadi; Celine Setio; Cristi Cristi; Debby Melandy; Erikka Erikka; Elin Elin; Jecky Jecky; Jessica Jessica; Kalvina Che; Khewin Khewin; Melanie Febrinova; Michelle Congstantia; Regina Michelle Hawidi; Stanley Yichunanto; Vina Marselina Natalia; Wisely Goh (National Conference for Community Service Project (NaCosPro), 2019)
The amount of waste continues to increase in Indonesia, making Indonesia become the second-largest contributor to plastic waste to the ocean in the world. In the city of Batam has recorded that the average amount of waste transported to the Punggur landfill is 900 tons per day and 20% of them are estimated to be a plastic waste. As the amount of rubbish increases, the final landfill for Batam City is rebuilt at a cost of up to 23 Billion Rupiah and is expected to accommodate household waste for the next 7-10 years. By looking at the low level of community concern for waste in the surrounding environment, through this society empowerment program we had the opportunity to conduct socialization and education to the residents of Block 3 in Kelurahan Lubuk Baja Kota regarding the importance of sorting and processing waste using solution of Eco brick. After this SEPORA activity, it is expected to be able to provide benefits for local residents to independently begin to do waste sorting from home and to process plastic waste by Eco brick, so that the amount of waste in Batam City is at least able controlled and managed by the local community.